The functions of contracts in interorganizational relationships: A contract experts’ perspective - Anna Hurmerinta-Haanpää; Sampo Viding (Sage Publications, 2022)
Previous research has shown how contracts are used together with relational governance (RG) mechanisms to manage interorganizational relationships (IORs). Moreover, research has found that contracts are used in safeguarding, adapting, and coordinating business relationships. Based on the findings of an interview study with 24 contract experts, we argue that, in addition to safeguarding, adaptation, and coordination, firms use contracts to: codify their deals; steer their internal work; and plan, promote, and steer collaboration. On the one hand, when used intelligently, contractual techniques that reflect different functions can enhance IOR performance. On the other hand, the careless use of contracts can negatively affect RG and IOR performance. Our research has notable theoretical and managerial contributions, as it develops the theory of the functions of contracts and argues that the functions are fundamental to designing a contract that aims to complement RG and support IOR performance.